Platinum-cobalt alloy catalyst for fuel cell and preparation method of platinum-cobalt alloy catalyst

The preparation of platinum-cobalt alloy catalysts by using chemical reduction method of chloride-free compounds in the aqueous phase solves the problem of using chloride ions and organic solvents in traditional methods, and achieves efficient and environmentally friendly catalyst preparation, which is suitable for commercial applications of fuel cells.

CN119905603APending Publication Date: 2025-04-29ZHEJIANG TIANNENG HYDROGEN ENERGY TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411987714.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The use of chloride ions and organic solvents in the preparation method of traditional platinum-cobalt alloy fuel cell catalysts leads to increased environmental pollution and cost, and it is difficult to accurately control the alloy composition and proportion.

Method used

The reaction is carried out in the aqueous phase by using chloride-free compounds as reactants, and the platinum-cobalt alloy catalyst is prepared by chemical reduction of non-chlorinated ion compounds to avoid the use of chloride ions and organic solvents. A high catalytic activity catalyst is prepared by optimizing the preparation process and parameters.

Benefits of technology

The preparation of chlorine-free and organic solvent-free platinum-cobalt alloy catalysts is realized, which reduces environmental pollution and preparation costs, improves the performance and stability of the catalyst, and is suitable for commercial applications of fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905603A_ABST
    Figure CN119905603A_ABST
Patent Text Reader

Abstract

The invention discloses a platinum-cobalt alloy catalyst for a fuel cell and a preparation method thereof, and the preparation method comprises the following steps: (1) preparing a platinum-carbon catalyst by taking a platinum salt precursor and a carbon carrier as raw materials; (2) adding the prepared platinum-carbon catalyst into a cobalt nitrate solution, and uniformly dispersing; adding a sodium borohydride solution for reduction reaction, and drying to obtain a catalyst intermediate; and (3) performing high-temperature reduction on the catalyst intermediate in reducing gas to obtain the platinum-cobalt-carbon alloy catalyst with excessive cobalt, and (4) adding the platinum-cobalt-carbon alloy catalyst with excessive cobalt into an acidic aqueous solution, dispersing, carrying out heat-preservation reflux in the presence of inert gas, and drying to obtain the platinum-cobalt alloy catalyst. According to the invention, a simple chemical reduction method is adopted, chloride ions and organic solvents are not used in preparation, and the platinum-cobalt alloy catalyst with high catalytic activity is prepared by a cobalt nitrate solution with specific mass concentration (5-6%) and a specific reduction temperature (900-1000 DEG C) through a reduction and alloying one-step method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fuel cells, and in particular to a platinum-cobalt alloy catalyst for fuel cells and a preparation method thereof. Background Art

[0002] As the global energy crisis and environmental problems become increasingly serious, clean and efficient energy conversion technology has become a hot topic of research. Fuel cells, as a device that directly converts chemical energy into electrical energy, have shown broad application prospects in the fields of energy, transportation, and electricity due to their high energy conversion efficiency and low emissions.

[0003] Fuel cell catalysts play a vital role in fuel cells. They mainly promote the redox reaction in fuel cells, reduce the activation energy required for the reaction, and thus accelerate the reaction. At the same time, they can also improve the energy conversion efficiency and stability of fuel cells and extend the service life of fuel cells.

[0004] Platinum-carbon (Pt / C) catalysts are one of the most commonly used catalysts in fuel cells due to their high catalytic activity and stability. However, as a precious metal, the high cost of platinum limits the commercial application of fuel cells. Therefore, how to reduce the amount of platinum used while developing high-performance catalysts has become an important topic in fuel cell catalyst research.

[0005] Researchers began to explore the alloying of platinum with other metals, among which platinum-cobalt alloys have attracted much attention. Platinum-cobalt alloy catalysts combine the high catalytic activity of platinum with the excellent stability of cobalt, which can improve the durability and stability of the catalyst while ensuring the catalytic activity. In addition, platinum-cobalt alloy catalysts also have good anti-poisoning properties and can maintain stable catalytic activity in environments containing impurities such as sulfur and phosphorus. This makes platinum-cobalt alloy catalysts have broad application prospects in the field of fuel cells.

[0006] Traditional methods for preparing platinum-cobalt alloy fuel cell catalysts mainly include physical methods and chemical methods. The physical method mainly deposits platinum and cobalt elements on a carrier through physical means such as sputtering and evaporation to form an alloy catalyst. However, it is difficult to accurately control the alloy composition and proportion of the catalyst prepared by this method. The chemical method reduces platinum and cobalt elements in ionic form to form an alloy catalyst through chemical reduction, coprecipitation and other methods. Although the chemical method can prepare catalysts with relatively uniform particle distribution, it often involves the use of chloride ions and the participation of organic solvents. The presence of chloride ions may not only reduce the catalytic activity of the catalyst, but also damage the electrolyte membrane of the fuel cell. At the same time, the use of organic solvents not only increases the preparation cost, but also may pollute the environment. These problems limit the application of traditional preparation methods, and there is an urgent need to develop new chlorine-free and organic solvent-free preparation methods.

[0007] In order to overcome the limitations of traditional preparation methods, it is of great significance to develop a chlorine-free and organic solvent-free platinum-cobalt alloy fuel cell catalyst preparation method. This method can avoid the use of chloride ions and organic solvents, reduce environmental pollution and preparation costs. At the same time, by optimizing the preparation process and parameters, a platinum-cobalt alloy catalyst with high catalytic activity can be prepared to meet the performance requirements of fuel cells. Summary of the invention

[0008] In view of the above-mentioned deficiencies in the prior art, a method for preparing a fuel cell alloy catalyst is provided. The inventor uses non-chloride ion compounds as reactants and conducts the reaction in an aqueous phase, thereby avoiding the use of chloride ions and organic solvents. This method can improve the performance of the catalyst while reducing environmental pollution, which is in line with the concepts of green chemistry and sustainable development; another important aspect is that it can also reduce the preparation cost, which is conducive to the commercial application of fuel cell technology.

[0009] The specific technical solutions of the present invention are as follows:

[0010] In one aspect, the present invention provides a method for preparing a platinum-cobalt alloy catalyst for a fuel cell, comprising the following steps:

[0011] (1) Preparing a Pt / C catalyst using a platinum salt precursor and a carbon support as raw materials;

[0012] (2) adding the Pt / C catalyst prepared in step (1) to a cobalt nitrate solution and dispersing the mixture evenly; then adding a sodium borohydride solution to cause a reduction reaction, and drying the mixture to obtain a catalyst intermediate;

[0013] (3) reducing the catalyst intermediate in a reducing gas at high temperature to obtain a PtCo / C alloy catalyst with excess cobalt;

[0014] (4) adding a PtCo / C alloy catalyst with excess cobalt into an acidic aqueous solution for dispersion, then heat-retaining and refluxing under an inert gas, and drying to obtain the platinum-cobalt alloy catalyst for the fuel cell.

[0015] Furthermore, in step (1), the preparation method of the Pt / C catalyst comprises:

[0016] (1.1) dispersing the conductive carbon carrier in a nitric acid solution for heat treatment, filtering and washing, and then dispersing in a nitric acid solution to obtain a conductive carbon carrier dispersion;

[0017] (1.2) Dispersing the platinum salt precursor in a nitric acid solution, adding anhydrous ethanol, heating to 95-105° C. under an inert atmosphere, and refluxing for 3-5 hours to obtain a precursor solution;

[0018] (1.3) Add the conductive carbon carrier dispersion in step (1.1) to the precursor solution in step (1.2), mix well, add anhydrous ethanol, heat to 100°C under an inert atmosphere, and reflux for 7 hours. After the reaction is completed, a Pt / C catalyst is obtained.

[0019] Preferably, the conductive carbon carrier is any one of the following: carbon black EC300J, Vulcan XC72, Cabot FCX800, Cabot BP2000;

[0020] The platinum salt precursor is dinitrosodiammine platinum.

[0021] Furthermore, in step (1.1), the heat treatment conditions are: hydrothermal reaction at 150° C. for 3 hours; and filtration and washing until the conductivity of the filtrate is ≤10 μS / cm.

[0022] Furthermore, in step (1.2), after adding anhydrous ethanol, the volume ratio concentration of ethanol is 5%-20%;

[0023] In step (1.3), after adding anhydrous ethanol, the volume ratio concentration of ethanol is 6%-10%.

[0024] Furthermore, in step (1.3), the conductive carbon support dispersion in step (1.1) is added to the precursor solution in step (1.2) at a catalyst platinum loading of 50 wt%;

[0025] After heat preservation and reflux, the product is filtered, washed and dried;

[0026] The filtration and washing are performed until the conductivity of the filtrate is ≤5 μS / cm, the drying temperature is 100° C., and the drying time is more than 10 hours.

[0027] Preferably, in step (2), the mass ratio of the Pt / C catalyst to the cobalt nitrate solution is 1:1.1;

[0028] The mass fraction of the cobalt nitrate solution is 5%-6%;

[0029] The mass fraction of the sodium borohydride solution is 2%.

[0030] Preferably, in step (3), the reducing gas is a mixed gas containing 5% H2 and 95% Ar in a volume ratio; the conditions for the high-temperature reduction are: high-temperature reduction at 900-1000°C for 30 minutes.

[0031] The present invention is completed in one step of direct reduction + alloying at high temperature. Reduction and alloying are carried out simultaneously, and the reaction system is more complicated, requiring higher energy input to overcome the energy barrier of the reaction. The high temperature of 900℃-1000℃ can provide sufficient thermal energy to make various substances in the reaction system have higher activity and reaction rate, accelerate the reduction of metal ions and the alloying process between platinum and cobalt atoms, promote the two to proceed synchronously, form a uniform and stable alloy structure, and help improve the activity and stability of the catalyst.

[0032] Specifically, in step (4), the acidic solution is a hydrochloric acid, sulfuric acid or nitric acid solution with a concentration of 1 mol / L, and the mass volume ratio of the cobalt-excess PtCo / C alloy catalyst and the acidic solution is 1:1.

[0033] Furthermore, in step (4), after heat preservation and reflux at 80°C, the product is filtered, washed and dried; wherein, the filtration and washing are repeated until the conductivity of the filtrate is ≤5μS / cm, the drying temperature is 100°C, and the drying time is more than 10 hours.

[0034] Beneficial effects of the present invention:

[0035] The present invention uses a simple chemical reduction method, does not use chloride ions and organic solvents in the preparation process, optimizes the preparation process and reaction conditions, and uses a cobalt nitrate solution with a specific mass concentration combined with a specific reduction temperature for reduction + alloying to prepare a platinum-cobalt alloy catalyst with high catalytic activity in a one-step method. The entire process does not require complex equipment and operations, avoids environmental pollution and cost increase problems, and makes the present invention have broad prospects in industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The present invention is a flow chart of the preparation process of the platinum-cobalt alloy fuel cell catalyst.

[0037] Figure 2 This is a graph showing the cyclic voltammetry test results of the present invention. DETAILED DESCRIPTION

[0038] Example 1

[0039] A method for preparing a fuel cell alloy catalyst, the preparation process flow chart is as follows Figure 1 As shown, the specific steps include:

[0040] 1. Weigh the carbon carrier EC300J at a mass fraction of 1%, disperse it in a 0.8M nitric acid solution, and then transfer it to a hydrothermal reactor and keep it at 150°C for 3h. After the reaction is completed, filter and wash until the filtrate conductivity is ≤10μS / cm, and disperse it in a 0.1M nitric acid solution to obtain a conductive carbon carrier dispersion.

[0041] 2. Add the reducing agent anhydrous ethanol to the dinitrodiammineplatinum nitric acid aqueous solution until the volume concentration becomes 13%. Heat to 100°C under nitrogen protection, keep reflux for 3 hours, and then cool to room temperature. The solution is yellow and transparent, and the precursor solution is obtained.

[0042] 3. Add a conductive carrier dispersion to the above precursor solution at a catalyst platinum metal loading of 50wt%, and then add anhydrous ethanol as a reducing agent at 8% of the total volume of the current solution. Heat to 100°C under nitrogen protection, keep reflux for 7 hours, and after natural cooling, filter and wash the product until the filtrate conductivity is ≤5μS / cm. After drying, a platinum-carbon fuel cell catalyst is obtained.

[0043] 4. Prepare a 5% (0.18M) Co(NO3)2·6H2O solution, add the above-mentioned platinum-carbon fuel cell catalyst, and disperse it by ultrasonic for 2 hours to obtain a dispersion.

[0044] 5. Take 2% sodium borohydride by mass and dissolve it in deionized water to obtain a sodium borohydride solution.

[0045] 6. Slowly add the sodium borohydride solution dropwise to the dispersion in step 4, stir and react for 3 hours. After the reaction is completed, filter and wash the reaction product until the filtrate conductivity is ≤10μS / cm, and dry it at 100°C for 6 hours to obtain catalyst A.

[0046] 7. Catalyst A was heat treated at 900°C for 30 min in a 5% H2 / 95% Ar atmosphere to obtain a Co-excess PtCo / C alloy catalyst.

[0047] 8. Prepare 1 mol / L HNO3 solution, add PtCo / C alloy catalyst with excess Co in a mass-to-volume ratio of 1:1, ultrasonically disperse for 30 min, heat in a water bath at 80°C for 2 h, filter and wash the product after cooling until the filtrate conductivity is ≤5μS / cm, and dry to obtain fuel cell platinum-cobalt alloy catalyst A.

[0048] Example 2

[0049] The same experimental steps as in Example 1 were used to prepare the fuel cell platinum-cobalt alloy catalyst B by adjusting the concentration of the Co(NO3)2·6H2O solution in step (4) to 6%.

[0050] Example 3

[0051] The experimental steps are the same as those of Example 1. In step (7), catalyst A is heat treated at 1000° C. for 30 min in a 5% H2 / 95% Ar atmosphere to obtain a fuel cell platinum-cobalt alloy catalyst C.

[0052] Example 4

[0053] The experimental steps are the same as those of Example 2. In step (7), catalyst A is heat treated at 1000° C. for 30 min in a 5% H2 / 95% Ar atmosphere to obtain a fuel cell platinum-cobalt alloy catalyst D.

[0054] Comparative Example 1

[0055] The same experimental steps as in Example 1 were used, except that the Co(NO3)2·6H2O solution in step (4) was prepared to 4%, and in step (7) the catalyst A was heat treated at 700°C for 30 min in a 5% H2 / 95% Ar atmosphere to obtain a fuel cell platinum-cobalt alloy catalyst E.

[0056] Comparative Example 2

[0057] The experimental steps are the same as those of Example 1, except that the Co(NO3)2·6H2O solution in step (4) is prepared to 8%, and in step (7) the catalyst A is heat treated at 700°C for 30 min in a 5% H2 / 95% Ar atmosphere to obtain a fuel cell platinum-cobalt alloy catalyst F.

[0058] Comparative Example 3

[0059] The experimental steps are the same as those of Example 1, except that the Co(NO3)2·6H2O solution in step (4) is prepared to 8%, and in step (7) the catalyst A is heat treated at 800°C for 30 min in a 5% H2 / 95% Ar atmosphere to obtain a fuel cell platinum-cobalt alloy catalyst G.

[0060] Comparative Example 4

[0061] The same experimental steps as in Example 1 were used, except that the Co(NO3)2·6H2O solution in step (4) was prepared to 4%, and in step (7) the catalyst A was heat treated at 800°C for 30 min in a 5% H2 / 95% Ar atmosphere to obtain a fuel cell platinum-cobalt alloy catalyst H.

[0062] Comparative Example 5

[0063] The experimental steps are the same as those of Example 2. In step (7), catalyst A is heat treated at 500° C. for 30 min in a 5% H 2 / 95% Ar atmosphere to obtain a fuel cell platinum-cobalt alloy catalyst I.

[0064] Comparative Example 6

[0065] The operation was carried out with reference to the steps of Example 1 in the invention patent with publication number CN111755707A, except that the alloying temperature was increased to 900° C. to obtain a fuel cell platinum-cobalt alloy catalyst J.

[0066] Test Example 1

[0067] The platinum-cobalt alloy catalysts prepared in Examples 1-4 and Comparative Examples 1-6 were subjected to cyclic voltammetry tests respectively, and the test methods were as follows:

[0068] Accurately weigh 5 mg ± 0.03 mg of catalyst.

[0069] 2 ml of deionized water, 2 ml of isopropanol and 50 μL of 5% Nafion solution were added to the weighed catalyst in sequence, and the slurry was evenly mixed by ultrasonic dispersion to obtain ink.

[0070] Take 5 μL of the dispersed ink and evenly drop it onto the smooth and clean surface of the glassy carbon electrode. Let it dry completely under an infrared lamp. Repeat this operation twice to prepare the working electrode. The saturated calomel electrode is the reference electrode and the platinum sheet is the counter electrode.

[0071] The three electrodes were placed in a 0.5M H2SO4 solution saturated with N2, first activated and stabilized at a scan rate of 50mv / s, and then cyclic voltammetry was performed at a scan rate of 20mv / s from 0V to 1.1V in the forward direction. The test results are shown in Figure 2. Figure 2 The hydrogen desorption peak is integrated to obtain the area S, and the electrochemical active area ECSA is calculated according to the following formula, as shown in Table 1.

[0072]

[0073] Among them, S H is the peak integrated area of ​​the hydrogen region, in C; V is the scanning speed, in V / s; M PtCo is the mass of platinum in the platinum-cobalt alloy on the electrode surface, in g; 0.21 is the coefficient, in mC / cm 2 ; The final ECSA unit is m 2 / g.

[0074] Table 1

[0075] catalyst <![CDATA[Electrochemically active area / m 2 / g]]> Example 1 A 63 Example 2 B 65 Example 3 C 65 Example 4 D 68 Comparative Example 1 E 32 Comparative Example 2 F 43 Comparative Example 3 G 47 Comparative Example 4 H 40 Comparative Example 5 I 31 Comparative Example 6 J 28

[0076] It can be seen from the results in Table 1 that in the process of preparing the alloy catalyst, Examples 1-4 used ethanol reducing agent, 5%-6% mass concentration of Co(NO3)2·6H2O solution, and heat treatment at 900-1000°C in a reducing atmosphere to successfully prepare a platinum-cobalt alloy catalyst with a large electrochemical area.

[0077] When the mass concentration of Co(NO3)2·6H2O solution increases or decreases and the heat treatment temperature decreases, the performance of the platinum-cobalt alloy catalyst will be greatly affected.

[0078] At the same time, the embodiments of the present invention are all completed in one step of direct reduction + alloying at high temperature. Reduction and alloying are carried out simultaneously, and the reaction system is more complicated, requiring higher energy input to overcome the energy barrier of the reaction. The high temperature of 900℃-1000℃ can provide sufficient thermal energy to make various substances in the reaction system have higher activity and reaction rate, accelerate the reduction of metal ions and the alloying process between platinum and cobalt atoms, and promote the two to proceed better synchronously, forming a uniform and stable alloy structure, which is beneficial to improve the activity and stability of the catalyst.

[0079] In Comparative Example 6, high-temperature reduction is first performed before high-temperature alloying. When the alloying temperature is raised to 900°C, the catalyst performance is very poor. The reason is that after the previous high-temperature reduction, the metal platinum and cobalt have been reduced to a single substance state. At this time, if alloying is performed at such a high temperature of 900°C, the excessively high temperature will cause the thermal motion of the atoms to be too intense, resulting in serious agglomeration between the formed platinum and cobalt metal particles, making the particle size larger and the specific surface area smaller. The active sites of the catalyst are often distributed on the surface of the particles. The reduction in the specific surface area will lead to a significant reduction in the number of exposed active sites, thereby reducing the performance of the catalyst.

Claims

1. A method for preparing a platinum-cobalt alloy catalyst for a fuel cell, characterized in that: The following steps are involved: (1) Preparing a Pt / C catalyst using a platinum salt precursor and a carbon support as raw materials; (2) adding the Pt / C catalyst prepared in step (1) to a cobalt nitrate solution and dispersing the mixture evenly; then adding a sodium borohydride solution to cause a reduction reaction, and drying the mixture to obtain a catalyst intermediate; (3) reducing the catalyst intermediate in a reducing gas at high temperature to obtain a PtCo / C alloy catalyst with excess cobalt; (4) adding a PtCo / C alloy catalyst with excess cobalt into an acidic aqueous solution for dispersion, then heat-retaining and refluxing under an inert gas, and drying to obtain the platinum-cobalt alloy catalyst for the fuel cell.

2. The method for preparing a platinum-cobalt alloy catalyst for a fuel cell according to claim 1, characterized in that: In step (1), the preparation method of the Pt / C catalyst comprises: (1.1) dispersing the conductive carbon carrier in a nitric acid solution for heat treatment, filtering and washing, and then dispersing in a nitric acid solution to obtain a conductive carbon carrier dispersion; (1.2) Dispersing the platinum salt precursor in a nitric acid solution, adding anhydrous ethanol, heating to 95-105° C. under an inert atmosphere, and refluxing for 3-5 hours to obtain a precursor solution; (1.3) Add the conductive carbon carrier dispersion in step (1.1) to the precursor solution in step (1.2), mix well, add anhydrous ethanol, heat to 100°C under an inert atmosphere, and reflux for 7 hours. After the reaction is completed, a Pt / C catalyst is obtained.

3. The method for preparing a platinum-cobalt alloy catalyst for a fuel cell according to claim 2, characterized in that: The conductive carbon carrier is any one of the following: carbon black EC300J, Vulcan XC72, Cabot FCX800, Cabot BP2000; The platinum salt precursor is dinitrosodiammine platinum.

4. The method for preparing a platinum-cobalt alloy catalyst for a fuel cell according to claim 2, characterized in that: In step (1.1), the heat treatment conditions are: hydrothermal reaction at 150°C for 3h; The product was filtered and washed until the conductivity of the filtrate was ≤10μS / cm.

5. The method for preparing a platinum-cobalt alloy catalyst for a fuel cell according to claim 2, characterized in that: In step (1.2), after adding anhydrous ethanol, the volume concentration of ethanol is 5%-20%; In step (1.3), after adding anhydrous ethanol, the volume concentration of ethanol is 6%-10%.

6. The method for preparing a platinum-cobalt alloy catalyst for a fuel cell according to claim 2, characterized in that: In step (1.3), the conductive carbon support dispersion in step (1.1) is added to the precursor solution in step (1.2) at a catalyst platinum loading of 50 wt%; After heat preservation and reflux, the product is filtered, washed and dried; The filtration and washing are performed until the conductivity of the filtrate is ≤5μS / cm, the drying temperature is 100°C, and the drying time is more than 10 hours.

7. The method for preparing a platinum-cobalt alloy catalyst for a fuel cell according to claim 1, characterized in that: In step (2), the mass ratio of the Pt / C catalyst to the cobalt nitrate solution is 1:1.1; The mass fraction of the cobalt nitrate solution is 5%-6%; The mass fraction of the sodium borohydride solution is 2%.

8. The method for preparing a platinum-cobalt alloy catalyst for a fuel cell according to claim 1, characterized in that: In step (3), the reducing gas is a mixed gas containing 5% H2 and 95% Ar in a volume ratio; The high temperature reduction conditions are: high temperature reduction at 900-1000° C. for 30 minutes.

9. The method for preparing a platinum-cobalt alloy catalyst for a fuel cell according to claim 1, characterized in that: In step (4), the acidic solution is hydrochloric acid, sulfuric acid or nitric acid solution with a concentration of 1 mol / L. The mass volume ratio of the PtCo / C alloy catalyst with excess cobalt to the acidic solution is 1:

1.

10. The method for preparing a platinum-cobalt alloy catalyst for a fuel cell according to claim 1, characterized in that: In step (4), after heat preservation and reflux at 80° C., the product is filtered, washed and dried; The filtration and washing are repeated until the conductivity of the filtrate is ≤5 μS / cm, the drying temperature is 100° C., and the drying time is more than 10 hours.

Citation Information

Patent Citations

  • Platinum-cobalt alloy catalyst and preparation method thereof

    CN111092235A

  • Preparation method of platinum-cobalt alloy catalyst

    CN111755707A

  • Platinum-cobalt alloy carbon catalyst for proton exchange membrane fuel cell and preparation method of platinum-cobalt alloy carbon catalyst

    CN113540481A

  • Pt / C catalyst and preparation method and application thereof

    CN114171749A

  • Preparation and application of platinum-cobalt alloy catalyst

    CN114570384A